Konsep Therapeutic Community : Penerapan Double Skin Fasade dan Skylight pada Desain Pusat Rehabilitasi Narkoba dinKabupaten Gowa - Abdurrahman Shaleh; Marwati, Marwati; Hildayanti, Andi (TIMPALAJA : Architecture Student Journals, 2026)
Drug abuse in Indonesia, particularly in Gowa Regency, poses serious risks to physical and psychological health, highlighting the need for effective rehabilitation facilities. This study aims to evaluate the implementation of the Therapeutic Community concept in the design of a Drug Rehabilitation Center, integrating architectural elements such as Double-Skin Façades and skylights to create an environment that supports patient recovery. The research employs a descriptive and comparative approach, analyzing architectural elements applied in a case study and comparing findings with relevant literature. Results indicate that double-skin façades with various materials, including Aluminium Composite Panel, wood, and GRC, effectively regulate temperature, lighting, and acoustics. Installing horizontal skylight windows enhances natural lighting, creating bright, comfortable spaces that support patients’ psychological well-being. The integration of these design elements strengthens social interaction and community activities in line with the Therapeutic Community principles, while also improving energy efficiency and building aesthetics. The study concludes that strategic integration of architectural elements can create functional, safe, and sustainable rehabilitation facilities, serving as a model for the development of similar centers in Indonesia